RETENSI FENOLAT BUBUR INSTAN FUNGSIONAL SELAMA PENYIMPANAN PADA SUHU RUANG - Nurakhirawati Nurakhirawati; Nurhaeni Nurhaeni; Irpan Irpan (KOVALEN: Jurnal Riset Kimia, 2016)
Fenolat retention of porridge instant functional for storage at room temperature. Has been done this study aims to determine the retention of instant porridge phenolics during storage as well as to determine the shelf life of instant porridge at room temperature. Estimation of shelf life or expiration period using the model of reaction kinetics. The treatment phase of the study include purple sweet potato flour manufacture, processing, instant porridge, instant porridge and storage at room temperature. Analysis of phenolics in instant porridge be done every 7 days for 56 days using UV-Vis spectrophotometry at a wavelength of 765 nm. The data obtained is used to determine the shelf life of instant porridge. The results obtained show the retention levels of phenolics on day 0 was 100% and at day 56 was 27.911% and the expiration of a functional instant porridge is 55 daysKeywords: Phenols, functional porridge, Fenolat Retention, Shelf Life, reaction kinetics model